Influence of physician networks on prescribing a new ingredient combination in heart failure: a longitudinal claim data-based study - Arnold, Christine; Koetsenruijter, Jan; Forstner, Johanna; Peters-Klimm, Frank; Wensing, Michel (Implementation science, 2021)
Background Since 2016, the combination of sacubitril/valsartan, which combines an angiotensin receptor and neprilysin inhibitor (ARNI), has been recommended in the guidelines for the treatment of heart failure. The adoption of new drugs may be influenced by collaboration and exchange between physicians. We aimed to determine whether characteristics of the professional networks of prescribing physicians were associated with the prescribing of ARNI in Germany. Methods We conducted a longitudinal analysis based on claims data in 2016-2018 in Germany. The characteristics of ambulatory care physicians' networks were determined in the analysis of the patient-sharing networks of physicians in 2017. Binary logistic regression analysis with the outcome 'prescribes ARNI in 2018' (present or absent) was carried out, using network characteristics as predictors, adjusted for specialty and sociodemographic characteristics of physicians. Results The network analysis included 8370 physicians, who had 144,636 connections. Prescribers had more connections to other physicians compared to non-prescribers (median 31 vs. 23). Regression analysis showed that the numbers of linkages to prescribers of ARNI were positively associated with prescribing ARNI. For 6-10 connections, the average marginal effect (AME) was 0.04 (confidence interval [CI] 95% 0.01-0.06) and for > 10 links the AME 0.07 (CI 95% 0.05-0.10) compared to 0-5 connections to prescriber. Conclusion Physicians who shared patients with many other physicians were more likely to prescribe ARNI, independent of physicians' specialty. This suggested that collaboration and exchange on the basis of patient-sharing with other physicians influenced their medication prescribing decisions.